2008
DOI: 10.1111/j.1365-2699.2008.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Are small sedentary species affected by habitat fragmentation? Local vs. landscape factors predicting species richness and composition of land molluscs in Swedish conservation forests

Abstract: Aim  To investigate the relative role of local versus landscape factors for local species diversity of snails and slugs in conservation forests. In landscapes with small, isolated patches of semi‐natural habitats, many species that require large habitat areas have disappeared or are threatened. We asked whether small sedentary taxa that depend on local conditions, such as molluscs, are affected if total habitat area decreases in the landscape. Location  Temperate broadleaved and oak‐rich forest in southern Swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
0
42
0
Order By: Relevance
“…This was confirmed by the result of Mantel tests which showed that the species composition of plants, leafhoppers and true bugs on each fragment was highly correlated (Su et al 2004; but see Dormann et al 2007). In contrast, snail community composition was only weakly correlated with that of leafhoppers, presumably because of the high dispersal limitation in snails (Götmark et al 2008). Also, since the fragments did not display a nested species composition, i.e.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This was confirmed by the result of Mantel tests which showed that the species composition of plants, leafhoppers and true bugs on each fragment was highly correlated (Su et al 2004; but see Dormann et al 2007). In contrast, snail community composition was only weakly correlated with that of leafhoppers, presumably because of the high dispersal limitation in snails (Götmark et al 2008). Also, since the fragments did not display a nested species composition, i.e.…”
Section: Discussionmentioning
confidence: 95%
“…This can be explained by their low mobility, making connectivity and the surrounding landscape less important for them. They can be expected to be more influenced by local habitat factors like management and management history (Boschi and Baur 2007; but see Götmark et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Honek and Martinkova (2010) showed that the invasive slug A. lusitanicus prefers to hide in dense stands of grass like the sown wild flower area from where it spreads into bordering fields or habitats for feeding. On the other hand, on a landscape scale, habitat fragmentation has been shown to negatively affect gastropod species (Gotmark et al 2008, Kappes et al 2009). In general, the strength of fragmentation effects depends on the mobility behavior of the species (Ewers and Didham 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Snail studies conducted in different forest associations (Addison andBarber 1997, Niemela 1997) indicated that terrestrial snails were strongly dependent on litter composition and were the most abundant in multispecies deciduous forests. According to Götmark et al (2008), studies carried out in 25 forest reserves indicated that pH of the litter was the most important factor decisive for the composition and abundance of snails. The malacofauna of the Malik Hill inhabits three different plant communities (hornbeam-beech woods, coniferous forest and meadow) growing on distinct soil types: rendzinas developed on Devonian dolomites, sandy rusty podzolic soils and gley soils which have been exposed to anthropogenic pressure for many years.…”
Section: Discussionmentioning
confidence: 99%